The advancement in irrigation solution within the field of endodontics, A Review - Fahad , Fatima; Al-Hashimi , Raghad A; Hussain , Munther J (Journal of Baghdad College of Dentistry, 2024)
The purpose of endodontic treatment is to eliminate all germs, microbial by-products, and vital tissues from the root canal system. Root canals can be mechanically and chemically used for this purpose. The needs and details of the irrigation solutions are described in this article. Because of its wide range of antibacterial activities and its ability to dissolve organic tissues, sodium hypochlorite is suggested as the main irrigation. On the contrary, chelation solutions are recommended as supplemental treatments to either eliminate the smear layer or prevent it from forming on the dentin surface. Data: Only articles that were published electronically were searched within the review. Sources: ‘Google Scholar’ and "Pub-med" websites were used to search data, The most papers related to the topic were chosen, specifically original articles , including only articles from 1999 to 2023.Journal papers that weren't published in a highly regarded publication, irrelevant studies, editorials, personal viewpoints, and social media sources were all disqualified from consideration. 98 articles were retained after the filtering procedure. In conclusion, this article reviews many types of new irrigations that may be used in endodontic practice in the future.